The debate between the Baṣrah and Kūfah Schools in Naḥw: A critical discourse analysis of political interests - M. Abdul Hamid; Segaf Baharun; Lateef Onireti Ibraheem; Kaharuddin; Muhamad Syahril; Ubay Ubay (Universitas Syiah Kuala, 2026)
The language contains an ideology that is connected to power and domination. This is because language is used depending on a particular ideological point of view and the actions of those holding power. Likewise, the differences in the schools’ (understandings) of Naḥw Baṣrah and Kūfah are also influenced by their users’ ideology and power dominance. Therefore, this study discusses the ideological dimensions and political interests in the debate between the schools of Naḥw Baṣrah and Kūfah. This study uses the critical discourse analysis (CDA) method on the corpus of literature and dialogues of central figures, such as Sībawayh and al-Kisāʾī, to discuss discursive practices that describe power construction and delegitimization strategies between schools. The results of this study indicate that the methodological differences between the normative Baṣrah and the flexible Kūfah are manifestations of ideological disputes and political interests that affect their legitimacy, not only linguistic. The delegitimization strategy is a symbolic domination tool to protect each group’s intellectual authority. Therefore, the implications of this research emphasize the urgency of estimating the ideological and political background in the study of Naḥw science, especially in interpreting the polemics of the Baṣrah and Kūfah schools, so that the linguistic approach can be more comprehensive and critical of the socio-historical context.